Determinants of Quality of Family Planning Counseling among Private Health Facilities in Lagos. Issue 3 (2nd August 2016) - Johnson, Doug; Ugaz, Jorge
Abstract : We use a unique dataset that includes an objective measure of the quality of family planning counseling from 927 private health facilities in Lagos State, Nigeria, to determine which variables at the facility and provider levels are most closely correlated with the quality of family planning counseling. Our data on quality come from mystery client surveys in which the clients posed as women seeking family planning counseling. We find that quality is strongly associated with the cadre of provider, with doctors delivering substantially higher‐quality counselling than nurses. Doctors not only outperform nurses overall, but also perform better on each category of quality and spend nearly three minutes longer on average counseling the mystery client. Location, fees charged for the service, and facility type are also strongly correlated with quality. The degree to which a facility specializes in family planning and facility size are only weakly predictive of quality.